Rhetorical move analysis in Political Science research article abstracts in English in Iranian journals - Seyed Paydari, Sara; Paramasivam, Shamala (Universiti Putra Malaysia Press, 2019)
Writing an abstract in English is a challenging task. This corpus-based study aims to identify the move structures of empirical Political Science research article abstracts written in English in Iranian journals and to examine if the writing complies with Hyland’s (2000) model as an accepted model for abstract writing. A corpus of 120 abstracts was randomly collected and analysed employing Hyland’s (2000) five-move model for abstract writing. Findings revealed that the moves of Political Science research article abstracts in Iranian journals differ from Hyland’s model. Political Science writers of Iranian journals used 3-move and 2-move patterns in their abstracts. These patterns show that the abstracts lack Move 1 (Introduction), Move 4 (Product) and Move 5 (Conclusion). These moves were low in frequency of use and were treated as optional. Only Move 2 (Purpose) and Move 3(Method) were used with high frequency. The move analysis showed that Iranian journals lack a display of genre competence in abstract writing with regard to the rhetorical structure of an abstract mainly in the use of moves that explain the introduction, outcomes and conclusions of research (i.e. Moves 1, 4 and 5 respectively). Recommendations are made to investigate reasons for the difference in move patterns through comparative and contrastive research between native writers (both in English and Persian languages) and non-native writers (Iranians writing in English), so as to address languages and discipline specific conventions in abstract writing in political science.